1985
DOI: 10.1002/bjs.1800720909
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate analysis of clinical and pathological variables in prognosis after resection of large bowel cancer

Abstract: Data on 709 patients who had a resection for colorectal carcinoma at Concord Hospital between 1971 and 1980 were studied to determine the independent effects on survival of several patient characteristics and pathological variables using the Cox regression model. Clinicopathological stage had the strongest association. Other variables ranked according to their relative importance independent of stage were: histological grade, level of direct spread, the presence of venous invasion, age and sex of the patient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
190
3
16

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(230 citation statements)
references
References 15 publications
21
190
3
16
Order By: Relevance
“…Some studies conducted on CA 19-9 reported that it was of greater sensitivity than CEA in case of advanced stage diseases (Wang et al, 2002;Mourtzikou et al, 2012). On the other hand, there are studies reporting that CEA had greater sensitivity (Chapuis et al, 1985;Von Kleist, 1986;Filella et al, 1992). Xavier et al's prior study reported that while CEA was a more sensitive measure than CA 19-9, it did not have prognostic significance and that CA 19-9 was the only factor independently associated with PFS (Filella et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies conducted on CA 19-9 reported that it was of greater sensitivity than CEA in case of advanced stage diseases (Wang et al, 2002;Mourtzikou et al, 2012). On the other hand, there are studies reporting that CEA had greater sensitivity (Chapuis et al, 1985;Von Kleist, 1986;Filella et al, 1992). Xavier et al's prior study reported that while CEA was a more sensitive measure than CA 19-9, it did not have prognostic significance and that CA 19-9 was the only factor independently associated with PFS (Filella et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…American Pathology Association reported the following conditions proven to have prognostic importance for colorectal cancers: local tumor size indicating the depth of tumor penetration (Chapuis et al, 1985), number of regional lymph nodes (Washington, 2010), presence of mesenteric lymph nodes also described as accumulation of satellite tumors according to 2010 tumor-lymph nodemetastasis (TNM) classification (Edge et al, 2010), vascular invasion (Michelassi et al, 1991), presence of residual tumor following curative treatment (Compton et al, 2000), and pre-operative CEA levels (Park et al, 2009). A recent study reported that while TNM staging was considered the most important prognostic for CRC, it was also emphasized that age, preoperative obstruction, CEA levels at time of diagnosis, resection condition, pathologic type, histologic grade, and lymphovascular invasion also had prognostic significance.…”
Section: Introductionmentioning
confidence: 99%
“…Adenocarcinomas are graded into well-, moderately or poorly differentiated tumors (grades 1, 2, 3, respectively) depending on the proportion of gland formation in the least differentiated component of the tumor away from the invasive edge, according to the World Health Organization (WHO) criteria [3]. Despite low levels of agreement among pathologists on this subjective assessment [4,5], histologic grading has been shown to be an independent prognostic factor for colorectal carcinoma [6][7][8][9]. This is particularly true for the poorly differentiated subgroup that has been most consistently found to be associated with adverse clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…O estádio clínico-patológico revelou ser a variável dominante independente que mais afeta a sobrevivência 6,7,8,9,10,11 , e poucos fatores foram identificados como tendo valor prognóstico independente do estadiamento de Dukes, tais como o grau de diferenciação celular e a invasão angiolinfática 12,13 . Contudo, a localização do tumor e a profundidade da invasão da parede intestinal também têm sido reportados como fatores prognósticos 14 .…”
Section: Introductionunclassified